Colistin: The phoenix Arises - JM Conly; BL Johnston (Canadian Journal of Infectious Diseases and Medical Microbiology)
The polymyxins were discovered in the 1940s and represent a group of closely related polypeptide antibiotics obtained from Bacillus polymyxa, which was originally isolated from soil (1,2). Although they have been used extensively worldwide in topical otic and ophthalmic solutions for decades, the intravenous formulations were gradually abandoned in most parts of the world in the early 1980s because of the reported high incidence of nephrotoxicity (3-5). As a result, the use of polymyxin preparations has been mainly restricted to the treatment of lung infections due to multidrug-resistant (MDR) gram-negative bacteria in patients with cystic fibrosis (6,7). The emergence of bacteria resistant to most classes of commercially available antibiotics and the shortage of novel antimicrobial agents with activity against gram-negative microorganisms have led to the reemergence of polymyxins as a valuable addition to the therapeutic armamentarium. It was thus considered timely to review colistin and its emerging role in managing infections due to MDR gram-negative bacteria.